The effect of different methods of primary pathogenetic prevention of dental caries immunity and antioxidant capacity of the oral health of the oil workers of the north of the Tomsk region (LLC "Endo Press", 2020)
The influence of different methods of primary pathogenetic prevention of dental caries in oil workers of the North of the Tomsk region on the immunity of the oral cavity and local antioxidant capacity. The most effective method was comprehensive prevention, which conducted the local deep fluoridation and prescribed immunomodulators and antioxidants. Reduction of growth of dental caries in this group was 49.6%. This was accompanied by improvement in immunity of the oral cavity and local antioxidant capacity